The synergistic antitumor effect of Huaier combined with 5-Florouracil in human cholangiocarcinoma cells - Zhaoyu Fu; Kexin Ma; Bing Dong; Chongyu Zhao; Chi Che; Chengyong Dong; Rixin Zhang; Haibo Wang; Xiang Wang; Rui Liang (BMC, 2019)
Abstract Background 5-Florouracil (5-FU) is a commonly used chemotherapeutic drug for cholangiocarcinoma, whereas it has unsatisfactory effect, and patients often have chemo-resistance to it. The combination of chemotherapeutic agents and traditional Chinese medicine has already exhibited a promising application in oncotherapy. Huaier extract (Huaier) has been used in clinical practice widely, exhibiting good anti-tumor effect. This paper aims to investigate the possibility of combination 5-FU and Huaier as a treatment for cholangiocarcinoma. Methods A series of experiments were performed on the Huh28 cells in vitro, which involved cell proliferation, colony formation, apoptosis, cell cycle, migratory and invasive tests. Besides, western blots were also performed to examine the potential mechanism of 5-FU. Results The combination effect (antagonism, synergy or additive) was assessed using Chou-Talalay method. Using the CCK-8 and Colony formation assay, the anti-proliferation effect of 5-FU combined with Huaier was observed. Apoptosis inducing and cell cycle arrest effect of the combination of two drugs were assessed by flow cytometry. To determine the combined treatment on cell immigration and invasion ability, wound healing and Transwell assay were performed. The above experiment results suggest that the combined 5-FU and Huaier, compared with treatment using either drug alone, exhibited stronger effects in anti-proliferation, cycle arrest, apoptosis-induced and anti-metastasis. Further, western blot results reveal that the inhibition of STAT3 and its target genes (e.g. Ki67, Cyclin D1, Bcl-2 and MMP-2) might be set as the potential therapeutic targets. Besides, the inhibition of combination treatment in proteins expression associated with proliferation, apoptosis, cell cycle and metastasis was consistent with that of previous phenotypic experiments. Conclusions Huaier combined with 5-FU exhibited a synergistic anti-tumor effect in Huh28 cell. Furthermore, the mechanisms might be associated with the activation and translocation of STAT3, as well as its downstream genes.